Platinum nanoclusters incorporated on zinc oxide nanosheets with enhanced mass activity for efficient hydrogen production - Khaled M. AlAqad (Chemical Physics Impact)
A two-step process using hydrothermal and chemical reduction methods was employed to integrate platinum nanoclusters onto zinc oxide nanosheets (ZnO NSs). The intense interaction between the nanoclusters (Pt) and ZnO NSs enhanced the electron transfer rate, resulting in exceptional electrocatalytic activity toward the HER and outstanding durability. In an acidic medium (0.5 M), the developed Pt/ZnO NSs electrocatalyst achieved an overpotential of -44 mV vs. RHE, affording a current density of -10 mA cm−2 with a low Tafel slope of 25 mV dec−1. The Pt/ZnO NSs electrode showed high mass activity (194.3 mA mg−1), 3.4-fold higher than the 20 % Pt/C (57.14 mA mg−1) at an overpotential of -44 mV. The turnover frequency of the Pt/ZnO NSs (0.52 s−1) is higher than that of the 20 % Pt/C (0.166 s−1) electrode. The impedance spectroscopy measurements investigated the strong coupling interaction between the platinum nanoclusters and ZnO NSs, which supports the high HER activity and facilitates electron transfer kinetics. Furthermore, the charge transfer resistance of the Pt/ZnO NSs is less than that of the 20 % Pt/C, which might be ascribed to the strong interaction between ZnO and Pt and the facile electron mobility from the conduction band of ZnO to Pt metal